Վրաստանի քաղաքական իրավիճակի նկարագրությունը Ստ. Բուռնաշևի պատմագիտական երկում - Մխիթարյան, Գոհար (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The article considers political condition of Georgia before conclusion of Georgievskiy treaty in 1783. The round of problems related to definition of the place of Georgia within the regional realities of 1750–1770s – relations of the King of Kartli-Kakheti Irakli II with Dagestan rulers and "Adrebijan khans" is presented in the article. The author shows influence of various factors on the process of Russian-Georgian rapprochement of 1760–1770s. The author has also revealed that the way to cooperation of the Russian-Georgian agreement was very complex and controversial. The article also gives a brief description of the Russian historical essay of the XVIII century by S.Burnashev "The Picture of Georgia or description of political state of the kingdoms of Kartali and Kakheti made by Colonel and cavalier Burnashev in Tiflis in 1786 for His Highness Irakli Temurazovich of Kartalin and Kakheti" and an extract from it is given. It is evident that during the description of the events S. Burnashev based first of all on his personal recollections and accounts of eyewitnesses. The author writes in great detail and clearly about those military and political events in the region where he himself took part or knows the information from first-hand accounts, but the text sometimes slips into a vague description when it comes to those events that the author knew by hearsay. This circumstance, of course, gives more credibility to this work. Most of the above information relates to the relationship between the Georgian kings Irakli II and Solomon I, military campaigns and raids of Dagestan troops in Georgia. At the same time, the source also contains a lot of information about political relations between King Irakli II of Kakheti and "the Khans of Adrebijan" as well as about the influence of Iran and Turkey on the situation in the region. These data allow us to reconstruct some episodes of military and political history of the South Caucasus in the XVIII century.
Keywords: Քաղաքական իրավիճակ